Pengaruh Perencanaan Pajak, Cash Holding, Profitabilitas, dan Ukuran Perusahaan terhadap Manajemen Laba - Christella, Brenda; Santo, Vianty Adella (Politeknik Ganesha Medan, 2024)
The growth of the global economy and the increasing competition in the business world, particularly after the Covid-19 pandemic, have motivated many parties to seize opportunities. Financial reports serve as a benchmark for the success or failure of a company's sustainability, with earnings management playing a crucial role in this context. The objective of this study is to determine whether tax planning, cash holding, profitability, and company size influence earnings management. This research is quantitative in nature, involving extensive numerical data that will be processed into statistical information. Secondary data from infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, totaling 65 companies, was used for this study. The purposive sampling method was employed for sample selection. The results of this study indicate that there is an influence of the independent variables, namely tax planning and company size, on the dependent variable, which is earnings management. It was also found that there is no influence of the independent variables, namely cash holding and profitability, on earnings management. Based on these findings, it is recommended to investigate other variables not examined in this study to provide broader insights and knowledge regarding factors affecting earnings management, making future research more varied. For infrastructure sector companies, strengthening internal oversight is necessary to reduce earnings management activities, which will ultimately enhance the company's image in the eyes of stakeholders.